Direct intramolecular carbon(sp2)–nitrogen(sp2) reductive elimination from gold(iii). Issue 18 (16th April 2019) - Kim, Jong Hyun; Mertens, R. Tyler; Agarwal, Amal; Parkin, Sean; Berger, Gilles; Awuah, Samuel G.
Abstract : The reactivity of bidentate Au III –Cl species, [(C^N)AuCl2 ], with a bisphosphine or carbon donor ligands results in reductive elimination. Abstract : The reactivity of bidentate Au III –Cl species, [(C^N)AuCl2 ], with a bisphosphine or carbon donor ligands results in reductive elimination. Combined experimental and computational investigations lead to the first evidence of a direct intramolecular C(sp 2 )–N(sp 2 ) bond formation from a monomeric [(C^N)AuCl2 ] gold(iii ) complex. We show that bidentate ligated Au(iii ) systems bypass transmetallation to form C(sp 2 )–N(sp 2 ) species and NHC–Au–Cl. Mechanistic investigations of the reported transformation reveal a ligand-induced reductive elimination via a key Au III intermediate. Kinetic studies of the reaction support a second-order rate process.